1996
DOI: 10.1097/00000539-199607000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Effects of Enflurane on Coronary Blood Flow, Myocardial Oxygen Consumption, and Myocardial Segmental Shortening in In Situ Canine Hearts

Abstract: This study evaluated changes in coronary blood flow (CBF), myocardial oxygen consumption (MVo2), and myocardial segmental shortening (SS) during intracoronary administrations of enflurane in in situ canine hearts. The left anterior descending coronary artery (LAD) of 11 anesthetized and mechanically ventilated dogs was perfused at constant perfusion pressure (80 mm Hg) with enflurane-free blood or with blood equilibrated in an extracorporeal oxygenator with enflurane (1.1%, 2.2%, 4.4%). CBF (measured with a Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It has been shown that volatile anaesthetics decrease Ca 2+ sensitivity in rat aortic vascular smooth muscle in vitro 19 and produce coronary vasodilation directly in in situ canine hearts. 20 However, the vascular responses to calcium chloride were similar in fentanyl±midazolam-and en¯urane anaesthetized dogs in the present study ( Fig. 4).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been shown that volatile anaesthetics decrease Ca 2+ sensitivity in rat aortic vascular smooth muscle in vitro 19 and produce coronary vasodilation directly in in situ canine hearts. 20 However, the vascular responses to calcium chloride were similar in fentanyl±midazolam-and en¯urane anaesthetized dogs in the present study ( Fig. 4).…”
Section: Discussionsupporting
confidence: 53%
“…Volatile anaesthetics have been shown to enhance recovery of postischaemic myocardium 33 and to produce coronary vasodilation directly in vivo. 20 En¯urane may have protected the myocardium against ischaemia and reperfusion injury, altering the response to calcium chloride. However, we observed that responses to calcium chloride in postischaemic myocardium were similar in en¯urane-and fentanyl±midazolam-anaesthetized groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Halothane may have some protective effects against ischemia and reperfusion injury of the myocardium and therefore altered the response to inotropic drugs. In addition, volatile anesthetics have been shown to directly produce coronary vasodilation in vivo (27). However, it has been demonstrated that responses to inotropic drugs under halothane anesthesia do not differ from those under fentanyl-midazolam anesthesia in postischemic myocardium in dogs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Gurevicius et al . [55] compared the inhalational agents' effects on coronary blood flow, myocardial oxygen consumption and myocardial segmental shortening. They found that isoflurane had a superior coronary vasodilating effect to halothane and enflurane, and that isoflurane was associated with less myocardial depression than enflurane.…”
Section: Myocardial Protection Offered By Alternative Anaesthetic Agentsmentioning
confidence: 99%